The flyers : - Adams, Noah (Random House Inc., 2003)
Adams traveled thousands of miles and interviewed scores of experts and individuals to piece together his story of Wilbur and Orville Wright. Adams helps us understand the talent and intensity of the brothers and their family, including the fascinating, deeply complex, and at times tragic bond between Orville and Katherine, his younger sister. The Flyer is a wonderfully rich narrative that brings an unprecedented spirit and immediacy to one of history's most dramatic stories